Role of inputs, institutions, and technical innovations in stimulating growth in Chinese agriculture - Fan, Shenggen; Pardey, Philip G. (International Food Policy Research Institute, 1995)
Recent attempts to quantify the sources of growth in Chinese agriculture have attributed an exceptionally large share of this growth to the contemporary institutional and market reforms within China. To analyze this important issue we use a newly constructed panel data set that includes an agricultural research or stock-of-knowledge variable. Our results suggest that while still a significant source of growth, the direct growth promoting consequence of institutional change and market reforms have been overstated by these earlier studies, even during the early stages of reforms that included the rapid introduction of the household production responsibility system. Research-induced technical change accounts for nearly 20% of the growth in aggregate agricultural output since 1965 although the share of growth attributable to technological innovation and changes in inputs and institutions varies considerably over time. Disaggregating the results within China also reveals substantial interregional variability in the sources of local growth, as would be expected in such a large and diverse country.